Fire and Its Interactions With Other Drivers Shape a Distinctive, Semi-Arid ‘Mallee’ Ecosystem - Clarke, Michael F.; Kelly, Luke T.; Avitabile, Sarah C.; Benshemesh, Joe; Callister, Kate E.; Driscoll, Don A.; Ewin, Peter; Giljohann, Katherine; Haslem, Angie; Kenny, Sally A.; Leonard, Steve; Ritchie, Euan G.; et al. (Frontiers in Ecology and Evolution, 2021)
Fire shapes ecosystems globally, including semi-arid ecosystems. In Australia, semi-arid ‘mallee’ ecosystems occur primarily across the southern part of the continent, forming an interface between the arid interior and the temperate south. Mallee vegetation is characterized by short, multi-stemmed eucalypt trees that grow from a basal lignotuber. Fire shapes the structure and function of mallee ecosystems. Using the Murray Mallee region in south-eastern Australia as a case study, we examine the characteristics and role of fire, the consequences for biota, and the interaction of fire with other drivers. Wildfires in mallee ecosystems typically are large (1000s ha), burn with high severity, commonly are stand-replacing, and create coarse-grained mosaics at a regional scale. Wildfires can occur in late spring and summer in any year. Recovery of plant and animal communities is predictable and slow, with regeneration of eucalypts and many habitat components extending over decades. Time since the last fire is a strong influence on many species and on the structure of communities. Animal species display a discrete set of generalised responses to time since the fire. Systematic field studies and modelling have revealed how spatial variation in fire regimes (‘pyrodiversity’) shapes biodiversity. Pyrodiversity includes variation in the extent of post-fire habitats, the diversity of post-fire age-classes and their configuration. At regional scales, a desirable mix of fire histories for biodiversity conservation includes a combination of early, mid and late post-fire age-classes, weighted towards later seral stages that provide critical habitat for many threatened species. Biodiversity is also influenced by interactions between fire and other drivers, including land clearing, rainfall patterns, herbivory and predation. Extensive clearing for agriculture has altered the nature and impact of fire, and facilitated invasion by pest species that modify fuels, fire regimes and post-fire recovery. Given the natural and anthropogenic drivers of fire, and the consequences of their interactions for the mallee biota, we highlight opportunities for conserving mallee ecosystems. These include learning from Indigenous knowledge of fire, implementing actions that consider synergies between fire and other processes, and strategic monitoring of fire, biodiversity and other drivers to guide place-based, adaptive management under climate change.